Migration in Kenya: Beyond Harris-Todaro - Cem Oyvat; Mwangi wa G\~ıth\~ınji (University of Massachusetts, Department of Economics, 2017)
This paper examines the impact of agrarian structures on the migration behavior and destination of rural household heads and individuals in Kenya. To explore the complexity of migration we extend the standard Harris-Todaro framework to account for land inequality and size. In addition, we disaggregate urban destination into different types of urban centers and also consider rural-to-rural migration. Using logistic regressions, we show that Kenyan household heads born in districts with higher land inequality, smaller per capita land and lower per capita rural income are more likely to migrate. Hence, poverty and inequality in Kenyan rural districts are transmitted to other areas over time. Our estimates also show that, for peasants whose incomes are squeezed by larger land inequality, migration from villages to suburban Nairobi, smaller cities, and villages in different districts could be a preferable strategy to migrating to Metro Nairobi. The impact of land inequality is more significant for male migration than female migration. Moreover, the level of education, age, marital status, gender, religion and distance to Nairobi play a role in the migration behavior of rural dwellers.
Keywords: O15; Q15; O12; O55; 330; migration; distribution; agrarian structures